The effects of anesthesia and fetal surgery on the early ovine fetus. Issue 3 (2014) - Manabe, Shutaro; Kitagawa, Hiroaki; Ooyama, Kei; Seki, Yasuji; Nagae, Hideki; Takagi, Masayuki; Koike, Junki; Zuccollo, Jane; Pringle, Kevin C
No abstract available